METODE ANALISIS KOMBINASI DETEKSI TEPI STUDI KASUS CITRA REOG KABUPATEN PONOROGO - Setiyo W, L. Anang (Widya Warta, 2011)
Image processing is now badly needed, especially in analyzing the level of doubt in the decision-making of an object / image. In decision-making, it is necessary to apply edge detection method. Today, a lot of edge detection methods can be used to conduct some analysis. Based on these issues, the writer tries to analyze the performance of edge detection by combining the already existing method. By the use of the combination of methods, it is expected that an edge detection method can be gained to serve as an alternative method. This case study was performed on the image of Reog of Ponorogo.